THE DERIVATIONAL SUFFIXES FOUND IN SCARLET LETTER NOVEL: A MORPHOLOGICAL ANALYSIS - Muhammad Seoultan Rabbani; Priyoto; Sahril Mujani (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2025)
This study focuses on finding out the type of derivational suffixes and the morphological process of derivational suffixes which is found in the novel Scarlet Letter chapter 1. Descriptive qualitative is the method used to identify the type and the morphological process of derivational suffixes. There are 33 data found in chapter 1 of the Scarlet Letter novel, including derivational suffixes Noun to Adjective 9 data (27,27%) such as: -ed, -en, -al, and -ful. Derivational suffixes Adjective to Adverb 9 data (27,27%) with the only suffix found which is; -ly. Derivational suffixes Verb to Noun 7 data (21,21%) such as: -er, -ment, -ive, -al, and -ion. Derivational suffixes Adjective to Noun 3 data (9,10%) including: -ty, -ance, and -ness. Derivational suffixes Verb to Adjective 4 data (12,12%) including: -ous, -ed, and -ing. The last is derivational suffixes Noun to Verb, 1 datum (3,03%) with the only suffix; -ize. The data that have the most occurrences are derivational suffixes Noun to Adjective and Adjective to Adverb with 9 occurrences each of them. Meanwhile, the data that has the fewest occurrence is derivational suffixes Noun to Verb with 1 occurrence.